Kaligono Village, A Home for Tree Snail Amphidromus (Gastropoda: Camaenidae) - Mujiono, Nova (ZOO INDONESIA, 2017)
During recent flora fauna surveys on the karst ecosystem in Purworejo regency, Central Java, opportunities were taken to document tree snails species in Kaligono village of district Kaligesing. Visual observation method was applied. Three species were recorded, namely Amphidromus furcillatus, Amphidromus heerianus, and Amphidromus perversus. The behaviour of these tree snails was also discussed briefly.